2021
DOI: 10.1002/edm2.250
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lifestyle Intervention on branched‐chain amino acid catabolism and insulin sensitivity in adolescents with obesity

Abstract: Results: Weight reduction was associated with reductions in BCAA, glutamate, and C3/C5 (p = .002) and increases in urea cycle AA (p = .029), suggesting an increase in BCAA catabolism. Increases in urea cycle AA during weight reduction were associated with increases in adiponectin, a marker of insulin sensitivity. Markers of insulin resistance (high BCAA, glutamate, and C3/C5 and low urea cycle AA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 53 publications
(131 reference statements)
2
30
0
Order By: Relevance
“…The ‘glutamate/glutamine’ analyte represents glutamate, plus an indeterminate contribution from hydrolysis of glutamine during acidic preparation of extracted metabolites for our flow injection‐tandem mass spectrometric assay 1–3 . Weight reduction and increases in insulin sensitivity in response to lifestyle intervention are accompanied by reductions in BCAA, C3/C5 acylcarnitines and glutamate/glutamine and increases in urea cycle intermediates, providing indirect evidence for an increase in BCAA catabolism 4 . It is currently unclear if an increase in BCAA catabolism is a cause or a consequence (or both) of the heightened insulin sensitivity associated with weight loss in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…The ‘glutamate/glutamine’ analyte represents glutamate, plus an indeterminate contribution from hydrolysis of glutamine during acidic preparation of extracted metabolites for our flow injection‐tandem mass spectrometric assay 1–3 . Weight reduction and increases in insulin sensitivity in response to lifestyle intervention are accompanied by reductions in BCAA, C3/C5 acylcarnitines and glutamate/glutamine and increases in urea cycle intermediates, providing indirect evidence for an increase in BCAA catabolism 4 . It is currently unclear if an increase in BCAA catabolism is a cause or a consequence (or both) of the heightened insulin sensitivity associated with weight loss in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Ratio C2/C0 was enhanced in patients with GC, which further indicated the increased fatty acyl mitochondrial transport and β-oxidation of fatty acids in GC 35 . Furthermore, it has been reported that short-chain carnitine-acylcarnitine translocase in mitochondria and short-chain acylcarnitine levels may be related to the metabolism of branched-chain amino acids (BCAA) 36 , and changed ratio of C3/C5 implicates altered flux through BCAA metabolic pathways 37 . The abnormal levels of short-chain acylcarnitines may further influence ratio Val/Phe.…”
Section: Discussionmentioning
confidence: 99%
“…In a lifestyle intervention study with 266 adults ( 15 ), a decrease in BCAAs in the intervention group was not associated with the change in analyzed glycemia measures after a 2-year follow-up. In adolescents (n = 33) the BCAA concentration was associated with insulin resistance after a 6-month lifestyle intervention ( 14 ), but the change in BCAA concentration during the intervention was not significant and no association between the changes in BCAAs and changes in glycemia measures from baseline was seen. A 7-day BCAA-restricted diet ( 16 ) decreased BCAA concentration and reduced insulin resistance in healthy volunteers (n = 12).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of intervention and control participants in the BCAA clusters did not differ either. Previous studies have detected that different lifestyle interventions ( 14 , 15 , 17 ) and weight-loss diets ( 33 ) have led to a decreased circulating BCAA concentration after a one-year follow-up. The absence of difference between the intervention and control group in our study might have been due to differences in the lifestyle intervention or lack of power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation